Essays on monetary and banking theory - Bertolai, Jefferson Donizeti Pereira (2012)
This thesis is dedicated to the study of both financial instability and dynamics in monetary theory. It is shown that bank runs are costless prevented in the standard model of banking theory when population is not small. An extension is proposed where aggregate uncertainty is more severe and fi nancial stability cost is relevant. Finally, transitions in the distribution of money are shown to be optimal in an economy where exchanges opportunities are scarce and heterogeneous. In particular, optimality of inflation depends on dynamic incentives provided by such transitions. Chapter 1 establishes the costless result for large economies by studying the e ffects of population size in the Peck-Shell analysis of bank runs. In chapter 2, dynamics optimality is studied in Kiyotaki-Wright monetary model when society is able to implement a inflationary policy. Despite adopting the mechanism design approach, this chapter parallels Sargent and Wallace (1981) analysis in highlighting dynamic incentives to the interaction between fiscal and monetary policies. Chapter 3 returns to the issue of financial stability by quantifying the costs involved in optimally designing a run-proof banking sector and by proposing an alternative information structure which allows for insolvent banks. Former analysis shows that optimal stability scheme features high long term interest rates, and the latter that imperfect monitoring can lead to bank runs with insolvency.